Ehrlichiosis in Southern Ohio: Two case reports and a review of the literature (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Tick-borne disease is becoming more commonplace as humans encroach on endemic regions with high tick preponderance. The incidence of ehrlichiosis is rising in conjunction with the increasing prevalence of its associated vector, Amblyomma americanum. In Ohio, populations of A. americanum have been expanding their range and growing in abundance and distribution. Southern Ohio in particular, has been identified as having a expanding population of E. chaffeensis infected ticks. The initial symptoms of ehrlichiosis are frequently vague and ill-defined. Often patients are not aware of having sustained a tick bite. Successful diagnosis and treatment of ehrlichiosis requires an index of suspicion, an awareness of local epidemiology, and prompt recognition of characteristic laboratory abnormalities consistent with E. chaffeensis infection. Patients in regions where these infections are known to exist, who present during tick season with fever, leukopenia and/or thrombocytopenia, and increased serum transaminase levels, should have ehrlichiosis included in the differential diagnosis. Left untreated, patients with ehrlichiosis can develop severe complications, including death. Doxycyline is the drug of choice for ehrlichiosis and should be initiated in symptomatic patients with a history of tick bite; it should not be withheld while awaiting lab results.
Keywords: Ehrlichiosis Ehrlichia chaffeensis Amblyomma americanum Tick-borne disease Ohio